2022
DOI: 10.1002/marc.202200196
|View full text |Cite
|
Sign up to set email alerts
|

Does the Size of Microgels Influence the Toughness of Microgel‐Reinforced Hydrogels?

Abstract: Rapid advances in the biomedical field increasingly often demand soft materials that can be processed into complex 3D shapes while being able to reliably bear significant loads. Granular hydrogels have the potential to serve as artificial tissues because they can be 3D printed into complex shapes and their composition can be tuned over short length scales. Unfortunately, granular hydrogels are typically soft such that they cannot be used for load‐bearing applications. To address this shortcoming, individual mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Lastly, it is important to note that as an alternative approach, dried microgels could be added to an interstitial precursor solution to form a granular hydrogel composite upon rehydration, which may overcome the impact of interstitial matrix dilution. [ 18 , 19 , 21 , 22 ] In this approach, drying and rehydration of microgels would have to be fully characterized to understand the impact on mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, it is important to note that as an alternative approach, dried microgels could be added to an interstitial precursor solution to form a granular hydrogel composite upon rehydration, which may overcome the impact of interstitial matrix dilution. [ 18 , 19 , 21 , 22 ] In this approach, drying and rehydration of microgels would have to be fully characterized to understand the impact on mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Amstad and colleagues fabricated polyacrylamide‐based granular hydrogel composites for 3D printing applications. [ 5 , 20 , 21 ] In another example, Poletti and colleagues developed poly(ethylene glycol)‐based (PEG) granular hydrogel composites consisting of PEG microgels and an interstitial matrix of either cellulose [ 22 ] or silk fibers [ 19 ] for further reinforcement. It has also been shown that granular hydrogel composites can greatly improve print fidelity when compared to bulk hydrogels without microgels.…”
Section: Introductionmentioning
confidence: 99%
“…In general, rheological properties of microgel suspensions depend on their shape, 32 size, 33 polydispersity, 28 stiffness, 34 and external conditions ( e.g. , temperature and pressure 23,35 ).…”
Section: Resultsmentioning
confidence: 99%
“…In general, rheological properties of microgel suspensions depend on their shape, 32 size, 33 polydispersity, 28 stiffness, 34 and external conditions (e.g., temperature and pressure 23,35 ). In this work, a close packing of relatively larger microgels provides a large interparticle contact area because of a higher microgel size dispersity, which generates increased friction between microgels in microgel suspensions.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we employ a multi-material microgel DIW printing method to fabricate the mechanochromic hydrogels in arbitrary shapes. The printing ink is composed of the microgels containing polymerizable monomers, which is prepared following similar procedures in the microgel printing methods. We first prepare a polyelectrolyte network embedded with mechanophores inside. The polyelectrolyte hydrogel is freeze-dried and ground.…”
Section: Introductionmentioning
confidence: 99%